Rapid evidence profile #45: What is known from evidence and from experiences in other jurisdictions about how to effectively and efficiently improve wait times for scheduled (elective) surgical services? - Waddell, K; Alam, S; Bhuiya, AR; Bain, T; Wilson, MG (My University, 2022)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about evidence and experiences in other jurisdictions about how to effectively and efficiently improve wait times for scheduled (elective) surgical services in response to a decision-maker’s request.
Keywords: jurisdictions; improve; wait times; elective; surgical services